IMPLEMENTASI TEKNIK RELAKSASI NAFAS DALAM UNTUK MENGURANGI NYERI AKUT PADA PENDERITA HIPERTENSI - Billa, Salsa; Panjaitan, Alya Azra; Batubara, Khairunnisa (LPPM AKPER GITA MATURA ABADI KISARAN, 2025)
Hypertension is a condition in which a person's blood pressure is higher than normal. This means that the blood pressure that pushes blood through the blood vessels is stronger than it should be, and can be at risk of causing damage to important organs such as the heart, brain, and kidneys. Normal blood pressure is 120/80 mmHg. Blood pressure is considered high if the systolic (upper number) is 140 mmHg and the diastolic (lower number) is 90 mmHg. Purpose to reduce acute pain in patients with hypertension. Method: the method used in compiling this case is a descriptive analytical method in the form of a case study for the approach process in applying deep breathing relaxation techniques. Results: The results of the study in patient I before the administration of deep breathing relaxation techniques, the pain experienced was on a scale of 8 (very severe). after giving deep breathing relaxation techniques, the pain became a scale of 2-3 (mild pain). in patient II before the administration of deep breathing relaxation techniques, the pain experienced was on a scale of 4-6 (moderate pain). After giving deep breathing relaxation techniques, the pain became a scale of 2-3 (mild pain). Conclusion: Open deep breathing relaxation techniques allow patients to reduce pain levels.